2015
DOI: 10.1007/s13762-015-0755-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling of TOC removal by H2O2/UV, photo-Fenton and heterogeneous photocatalysis processes to treat dye-containing wastewater

Abstract: Wastewater from textile manufacturing introduces recalcitrant organic compounds, such as dyes and toxic by-products into the environment, where advanced oxidation processes are used to treat toxic and non-biodegradable organic pollutants which cannot be removed by traditional methods. H 2 O 2 /UV, photo-Fenton and heterogeneous photocatalysis (TiO 2 /H 2 O 2 /UV) processes were used, and the effect of the hydraulic retention time on total organic carbon (TOC) removal was evaluated by fitting the analytical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The aforementioned hydroxyl radicals were strong oxidants, which was available to oxidize different organic dye components at low concentrations (Lopez‐Lopez et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The aforementioned hydroxyl radicals were strong oxidants, which was available to oxidize different organic dye components at low concentrations (Lopez‐Lopez et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Among these technologies, photolysis (chemical method), which is used as a potential technology for dye disposal, has demonstrated excellent degradation results for most types of dye waste water due to the generation of hydroxyl radical (•OH). The aforementioned hydroxyl radicals were strong oxidants, which was available to oxidize different organic dye components at low concentrations (Lopez-Lopez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the irradiated solution, there is competition between the parent pollutant and the formed intermediate compounds for oxidizing agents 55 . The base TiO 2 catalyst seems to have favoured the conversion of 4-t-BP, while the 4% Fe/TiO 2 catalyst clearly promoted the carbon oxidation to CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported that this combination increased the efficiency of the process, since UV light was combined with both the oxidant and the photocatalyst 59 , while others claimed that the efficiency of the process was reduced due to the competition for ultraviolet irradiation between the oxidant and the photocatalyst 60 or due to H 2 O 2 adsorption on the surface of catalytic particles, which reduced the activity of the catalyst 61 . In addition, it could be suggested that hydrogen peroxide was consumed at the beginning of the process, and the rest of the organic matter was removed by the catalyst 55 .…”
Section: Resultsmentioning
confidence: 99%
“…An alternative for the treatment of textile wastewater is the advanced oxidation processes (AOP) based on the generation of hydroxyl radicals, a powerful oxidizing agent, allowing the transformation of the pollutants into CO 2 , water, and inorganic ions or otherwise less complex compounds (Lopez‐Lopez et al, ). Since AOPs may have high costs to achieve high pollutant removal efficiencies, these treatments may be applied to enhance wastewater biodegradability, allowing the biological process to be used (Oller, Malato, & Sánchez‐Pérez, ; Soares et al, ).…”
Section: Introductionmentioning
confidence: 99%